Safety of Smart Cities - Prochazkova, Dana; Prochazka, Jan (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Present work is based on the concept of integral safety management of system of systems and it gives the proposal of set of measures into the simultaneously modern concept of communities called â€œsmart citiesâ€. The target is to ensure the safe smart city, i.e. the human community that will ensure the security and the development of their citizens under the conditions of normal, abnormal and critical. This demand is important because the mentioned diversity of life conditions is the result of both, the dynamic development of world and the human errors at control of behaviour of human society in the community.